Relationship Between Work Duration and Work Process with Low Back Pain Among Coffee Farmers - Ulfa Husna Dhirah; Hasratina, Illa (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: Low back pain (LBP) is a major occupational health concern among agricultural workers, yet evidence specific to smallholder coffee farmers regarding the combined impact of work duration and work processes remains limited, particularly in the context of developing economies like Indonesia. Methods: An analytical cross-sectional study was conducted from 1–13 October 2025 in Tunyang Induk Village, Indonesia. Using total population sampling, 135 coffee farmers participated. Data were collected through face-to-face interviews using a structured questionnaire that assessed sociodemographic variables, work duration (categorized as ≤8 hours or >8 hours/day), work processes (evaluated using an adapted Quick Exposure Check tool and categorized as